Vigilancia de la salud de los trabajadores expuestos a plaguicidas en el programa de control de vectores en México. - Ocotzi-Elías, María Isabel; Schilmann, Astrid; Arenas-Monreal, Luz (Salud Pública de México)
Objective. To analyze the interpretation and implementation of the policies for the worker's health surveillance in the vector control program in Mexico. Materials and methods. We conducted a cross-sectional study in four states of Mexico using mixed methods that include semi-structured interviews, data on pesticides applied and the workers' results for plasmatic acetylcholinesterase activity analysis collected from the states' registries. Results. We identified an extended and varied use of highly hazardous pesticides and different processes to monitor occupational exposure to acetylcholinesterase inhibitors in each state. None of the states calculated biological exposure indices. Conclusions. Knowledge of policies for workers' health surveillance needs to be strengthened and there is an urgent need to enhance the content of the existing policies to include the multiple, combined, and long-term occupational exposure of workers in the vector control program in Mexico.